Ultrasound-assisted green syntheses of novel pyrimidine derivatives and their comparison with conventional methods - Vergush A. Pivazyan; Emma A. Ghazaryan; Armen V. Karapetyan; Roza S. Shainova; Siranush V. Harutyunyan; Asya S. Vorskanyan; Aleksandr P. Yengoyan; Tiruhi A. Gomktsyan (Journal of Saudi Chemical Society)
Ultrasound-assisted green syntheses of novel potentially bioactive pyrimidine derivatives have been carried out. The same compounds were obtained by conventional methods of synthesis, and the reaction times and yields of final products obtained by these two methods were compared. It was found that the time of utrasound-promoted reactions was reduced by almost 6–96 times, and their yields were equal or turn out to be greater compared to the traditional approach. The synthesized compounds showed a pronounced stimulating effect on plant growth. The most active derivatives were selected for deeper biological studies and subsequent field trials.